Pendekatan TOGAF ADM pada Penyusunan Arsitektur Enterprise SMAN 16 Surabaya - Divani Jane Forinda Putri; Siti Mukaromah; Virdha Rahma Aulia (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This research aims to improve operational efficiency and quality of education services at SMAN 16 Surabaya through enterprise architecture design using the TOGAF ADM framework. The school faces challenges in operational management due to the lack of a structured and adequate system to support the digitization process. With a systematic methodological approach, this research includes the stages of literature review, data collection, and architecture development based on organizational needs, which include the preliminary phase, architecture vision, business architecture, information systems architecture, technology architecture, and opportunities & solutions. The results showed that the average implementation achievement reached 90.0%, with the main successes at the visioning, business architecture, and technology solution planning stages. Some of the priority solutions identified include digitizing administrative processes, integrating student data, and managing information technology infrastructure that supports learning. Also, the results of this research will provide a technology and information systems blueprint that summarizes system needs and candidate applications for each business process, providing integrated solutions and supporting the optimization of school operations as a whole.